Bridging the Gap in Cervical Cancer Triage: Experience from Field-based Colposcopy Services in Rural India - Anand G. Shah; Mohit Nareshbhai Makwana (Journal of Integrated Health Sciences)
Problem: Across the globe, cervical cancer is the second most common cancer among females. As per the World Health Organization, almost 90% of cervical cancer occurs in low- to middle-income countries. With the use of cytology and DNA tests, many cervical cancer cases are being diagnosed at an early stage; however, many of them go unattended as females do not turn for colposcopy examination. Approach: Medical Officers were trained in basics of colposcopy, and procedures were conducted in camps with a portable colposcopy machine. Local Setting: Every year, The Gujarat Cancer and Research Institute, a state cancer institute in Gujarat, India, conducts 70–80 cancer screening camps every year. Before the newer approach, all suspected females with cervical cancer were referred to our base institute for colposcopy examination. However, we demonstrate our experience of conducting colposcopy examinations in the field at the nearest health center to the beneficiary. Relevant Changes: Between January 2023 and May 2023, 70 females were identified with abnormal cytology and Human Papilloma Virus DNA test and were referred to our institute for colposcopy procedures. However, only 31% of the suspected female beneficiaries visited the institute for colposcopy. With the newer approach of conducting colposcopy camps in the beneficiary’s area, 58% of the remaining females have undergone the procedure. Lessons Learned: To scale our efforts in contributing toward the cervical elimination strategy, it is important to complete the colposcopy examination of suspected females. Our efforts demonstrated how establishing colposcopy camp as a door-to-door service can increase compliance for the procedure.